Pendampingan Pembelajaran Sains Intreraktif melalui Pengenalan Konsep Dasar Tata Surya pada Siswa MI Ma’arif Ngebel Ponorogo - Sari Fitri Nurjanah; Soni Amrullah (Social Science Academic, 2025)
The mentoring activities carried out at MI Ma'arif Ngebel aim to improve students' understanding of basic concepts, particularly the solar system and direct observation of the sun with a telescope. The problem stems from the need to introduce interactive learning that is expected to broaden students' knowledge and provide conceptual understanding through direct learning experiences. Through an interactive learning approach, it is hoped that students' interest and motivation to learn will increase. This study uses a qualitative approach combined with the Asset Based Community-driven Development (ABCD) approach. Data collection techniques include documentation, observation, and interviews. The results of this study show the enthusiasm and spirit of learning that students demonstrate at each stage of the activity. This activity received positive responses and appreciation from various parties, namely the school, students, and the collaboration team from the Reog Astronomy Club (RAC) Ponorogo.